Relentless innovation : what works, what doesn't--and what that means for your business - Phillips, Jeffrey, 1963- (McGraw-Hill, 2012)
Given today's business landscape-increasing customer demand, global competition, lower trade barriers-being good isn't enough. This groundbreaking guide provides the knowledge and tools you need to transform your organization from a well-run company to a relentlessly innovative company.